Carotid atherosclerosis : an ultrasonographic window for subclinical atherosclerotic cardiovascular disease - Dalan, Rinkoo (Nanyang Technological University, 2024)
Background : The global distribution for atherosclerotic cardiovascular disease (ASCVD) has been progressively shifting away from Western countries, toward Asia. Deaths from ASCVD are also more likely to occur prematurely (<70 years of age) in Asia. We need to improve the risk stratification of ASCVD in our population, to enable national efforts aimed at personalized prevention of ASCVD. One of the more advanced non-invasive methods of cardiovascular risk assessment is the measurement of carotid atherosclerosis using carotid ultrasonography. Most of the data regarding carotid ultrasonography is in Western countries with paucity of data in the Asians. Aims : The overarching aim is to understand carotid atherosclerosis and its determinants in the multi-ethnic population of Singapore to enable personalized predictive strategies. Aim 1: To develop a standardized protocol for measurement of carotid atherosclerosis and develop age, sex and ethnicity- stratified reference range in the multi-ethnic population of Singapore for carotid artery intima media thickness (CIMT). Aim 2: To study the inter-ethnic and inter-sex differences in the strength of association of cardiometabolic determinants with CIMT. A secondary aim is to study the association of cardiometabolic disease trait related polygenic risk scores and CIMT related polygenic risk score derived in the UK biobank in a subset of Chinese participants. Aim 3: To investigate metabolomics in relationship with CIMT independent of cardiometabolic risk factors and to study diet and genetic determinants of these pathways. Methods : Population: The Health for Life in Singapore study is a population cohort comprising the multi-ethnic Asian population of Singapore (primary ethnic groups: Chinese and other East Asians (76%), Malay and other South-East Asians (15%), Indian and other South Asians (9%). Participants completed a comprehensive, structured assessment including questionnaires, physiological measures, imaging assessments and biological sample collection. A total of 8762 participants who completed the carotid ultrasonography are included in this analysis. Carotid Ultrasonography: The protocol for the acquisition and measurements of the carotid atherosclerosis was developed and performed in the HELIOS study. CIMT measurements were taken from the distal common carotid artery at lateral and 21 posterior angles bilaterally during the end-diastolic phase and analysed using automated edge detection software. Mean of all 4 measurements was taken as avgCIMT and maximum as maxCIMT. Aim 1: A healthy population subset comprising 4996 individuals (Chinese: 74%, Malays: 12%, Indians: 14%), was used to derive the ethnicity sex and age stratified 75th centile values using fractional polynomial regression approach. A comparison was performed with a subset of super healthy participants as a sensitivity analysis to seek internal validity. Additionally, comparison was performed with normative values in Asian and European populations to seek external validity. Aim 2: Multivariable linear regression models were used to study associations with various cardiometabolic determinants adjusting for confounders. Interactions with sex and ethnicity were tested. Additionally using the data from PGS catalogue and UK biobank, we derived similar cardiometabolic trait specific polygenic risk score in a subset of Chinese participants and tested for associations with similar traits and with CIMT. Aim 3: We used data from untargeted metabolomics profiling of plasma samples performed by Metabolon. The food frequency questionnaire developed locally was used to determine the diet. Genetic links was determined from GWAS data from the HELIOS participants. Generalized linear model , adjusting for all traditional cardiovascular risk factors was used to identify the top metabolites in association with CIMT. Associations with diet and genetics was studied. Results : We derived reference equations to estimate ethnic- and sex-specific 75th centiles (95% CI) of CIMT. Framingham risk score and cardiometabolic risk factors are higher with CIMT more than 75th centile (p<0.001), compared to lower than 75th centile. Compared to European and American populations, the 75th centile values are lower in all Asian ethnic subgroups (p<0.001). The 75th centile also varied between ethnic subgroups and sex (P<0.001). We found significant inter-sex and inter-ethnic differences in the strength of association between traditional cardiometabolic risk factors (BMI and lipid variables) and CIMT. This shows the need for personalized therapeutic goals for cardiometabolic risk factor control in various ethnic groups. In Chinese sub-population, we found significant correlations of the cardiometabolic trait specific polygenic risk scores with CIMT , partially mediated through the traits in mediation analysis. This suggests causality for the traits. We also found modest associations of the CIMT trait specific polygenic risk scores (from UK Biobank). 22 This suggests similarities in genetic determinants of CIMT in the European and Chinese populations. We found 13 significant metabolites that associated with CIMT after adjustment for cardiometabolic risk factors. The metabolites from the vitamins and cofactors (1), fatty acid metabolites (6), and carbohydrate (1) pathways associated inversely with CIMT, whereas the metabolites from the plasmalogen (4) and caffeine (1) pathway associated positively. The metabolite correlated with characteristic dietary patterns. Methyl ascorbic acid and glycerate correlated with fruits intake, fatty acids with wholegrains, and plasmalogens with red meat consumption. Significant genetic links were found with variants in genes that determine enzymes that impact the metabolites concentrations. Conclusion: The derivation of equations allow determination of a personalized predicted 75th centile value in terms of age, sex and ethnicity. The differences in strength of association between risk factors and CIMT highlight the need for personalization of preventive care. Significant correlations of the cardiometabolic trait specific polygenic risk scores with CIMT suggests causality. The associations of the polygenic risk scores with the CIMT trait specific polygenic risk score in the UK biobank study also suggests similar genetic determinants of CIMT in the European and Chinese populations. Similar studies will be performed in the Malays and Indian participants with availability of data and will shed more light on the interethnic genetic differences. The metabolomic determinants of CIMT suggest characteristic associations with diet and links with genetic variations determining the related metabolic enzymes. These observations will be useful in devising a personalized nutritional recommendation (diet and supplements) and therapeutics and goals for cardiovascular risk factor control for prevention of ASCVD. With data on prospective outcomes, longitudinal evaluation will be performed to validate the utility of CIMT for predicting cardiovascular outcomes in our population.